ENHANCING STUDENTS’ INTERACTION SKILLS AND CRITICAL AND CREATIVE THINKING THROUGH MOVIES - Agelyia Murugan; Wan Noorli bt Razali (University of Kuningan, 2013)
Abstract: In the context of higher education in Malaysia, the aims are to produce competent Â and conï¬dent language users in the students who learn English as their second language. By incorporating movies in English language teaching, it will enable the students to learn English more actively, meaningfully and interactively. This study seeks to explore the potential use of movies as a teaching and learning tool in encouraging active participation and critical thinking in the English language classroom. The existence of technology in movies has made ways for the educators to do segmentations of the important parts in the movies for the limited classroom time. Critical thinking plays a vital role in education simply because of the personal and language enrichment. It also allows the students into self-directed thinking in making decisions more carefully, clearly and logically. It is important to incorporate the Universal Intellectual Standards of Critical Thinking Theory into the crucial foundation in encouraging active participation of students. It is believed that critical thinking will enable the students to engage themselves in their own pace of learning and provide greater freedom for expressing and arguments. Keywords: movies, active participation, critical thinking, universal intellectual standard